A CNH monolayer: a direct gap 2D semiconductor with anisotropic electronic and optical properties. Issue 33 (9th August 2017) - Yi, Wen-cai; Hu, Tao; Su, Tan; Islam, Rashed; Miao, Mao-sheng; Liu, Jing-yao
Abstract : Recently, two-dimensional materials have received significant attention due to their superior transport and optical properties and their potential roles in future nanoscale devices. Abstract : Recently, two-dimensional materials have received significant attention due to their superior transport and optical properties and their potential roles in future nanoscale devices. Compared to three-dimensional materials, there is still a lack of variety of 2D materials, especially with desired band gap. The number of wide gap 2D materials is quite limited. A good candidate is the well-known h-BN. However, this material has a gap of 5.56 eV, which is too high for a semiconductor, and its fabrication involves boron and nitrogen precursors, which are usually hard to process. In this study, using first principles calculations, we proposed a new 2D material (α-CNH) consisting of C, N, and H. It consists of array of polyethylene chains connected by N atoms in the perpendicular direction. Because of its framework formed by C–C and C–N bonds, α-CNH shows excellent stability and mechanical properties. It is a direct gap semiconductor with a band gap of 3.03 eV, as calculated by the hybrid functional, and exhibits interesting electronic and optical properties that are very anisotropic, as determined via its structure. The mobilities of both electrons and holes in this material are very anisotropic. The mobility along easy direction is 3 to 5 times higher than that along the hard direction. Interestingly, the high mobility directions of electrons and holes are different; this allows to design novel devices in which the high conducting directions can be altered by changing the carriers by applying gate voltage.